Oxygen-Ozone therapy for treatment of induced Ischemic Stroke in an in vitro animal model - Orlandin, Jéssica Rodrigues (2022)
Encephalic Vascular Accident, or stroke, is the most common pathology of the central nervous system in humans, being the second leading cause of death and physical and cognitive disabilities in developing countries. It is a vascular disorder, which may present in an ischemic (more common) or hemorrhagic form. Although there is still a lack of studies on the prevalence of strokes in animals, it is believed that the pathology is becoming increasingly common, mainly due to the habits and progressive age of dogs and cats. Ozone is oxidant gas, capable to oxidize double bonds of organic molecules, producing lipoperoxides and aldehydes. Among several other effects of ozone, we can mention the stimulation of the immune and antioxidant system and improvement in tissue vascularization and oxygenation. It has been previously shown that ozone therapy can be effective in neuromodulation, neuroprotection and nerve regeneration. The present study aims to evaluate the effect of ozone therapy treatment after induced cerebral ischemia. The experiment was divided into three stages: in vivo step (pilot study), carried out in Brazil; in vitro step performed with neuroblastoma lineage cells in Italy; and in vitro step performed with amniotic membrane stem cells, carried out in Brazil. The in vivo step, carried out in 5 rats as a pilot study was interrupted due to the high mortality rate and lack of gross results. The first in vitro step, performed with neuroblastoma lineage cells (SH-SY5Y) subjected to 24 hours of hypoxia in an incubator culture chamber and treatment with different concentrations of ozone (2 - 10 µg/mL) indicated a possible neuro regenerative effect of ozone at low concentrations. The same protocol was applied to canine amniotic membrane stem cells, that were evaluated by colorimetric assay spectrophotometry, fluorescence microscopy and flow cytometry. The results corroborated to the first step of the study, where cells treated with low ozone concentration (3 - 8µg/mL) had better metabolic conditions, lower apoptosis level and oxidative stress comparable to those cells that were not subjected to hypoxia. High concentrations of ozone (18-30 µg/mL) promote increased rates of apoptosis and cell death It is worth mentioning that we stipulated an unprecedented protocol that mimics ozone therapy for ischemic stroke, using ozonized culture medium after hypoxia induction. Although more studies are needed to open new venues for translational medicine, it is concluded that ozone has dose-dependent hormetic effect and at low concentrations and was able to reverse the effect of ischemia in vitro.